2022
DOI: 10.5194/isprs-archives-xliii-b2-2022-761-2022
|View full text |Cite
|
Sign up to set email alerts
|

From Scan-to-Bim to Heritage Building Information Modelling for an Ancient Arab-Norman Church

Abstract: Abstract. One of the most significant issues in Cultural Heritage is the management of ancient buildings to monitor their state of conservation or to plan actions in their maintenance; this issue can be now approached thanks to the use of the Scan-to-BIM process. This method allows the creation of parametric models into a BIM environment, which are capable of enhancing the geometrical representation of building elements and integrating different types of data.This paper shows the results of the research activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 3 publications
0
13
0
Order By: Relevance
“…Compared with existing approaches or studies, the developed digital interactive exploration platform blending BIM and virtual reality offers several distinct advantages and contributions. Firstly, while existing approaches utilize either BIM [15], [21]- [24] or virtual reality [25]- [29] separately for cultural heritage exploration, integrating both technologies in a cohesive platform provides a more comprehensive and immersive experience [30]- [32]. By leveraging the detailed 3D models and rich information from BIM and combining it with virtual reality's immersive and interactive capabilities, the platform offers a more holistic and realistic representation of historical places.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with existing approaches or studies, the developed digital interactive exploration platform blending BIM and virtual reality offers several distinct advantages and contributions. Firstly, while existing approaches utilize either BIM [15], [21]- [24] or virtual reality [25]- [29] separately for cultural heritage exploration, integrating both technologies in a cohesive platform provides a more comprehensive and immersive experience [30]- [32]. By leveraging the detailed 3D models and rich information from BIM and combining it with virtual reality's immersive and interactive capabilities, the platform offers a more holistic and realistic representation of historical places.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, on the other hand, examples of applications for the Scan-to-BIM method include studies such as Mellado et al [41], Nguyen et al [44], Qiu et al [45], and Aricò and Brutto [46], among others. In Mellado et al [41], a Scan-to-BIM approach was proposed to showcase how laser scanning technology can be employed for existing buildings to facilitate sustainable-oriented design.…”
Section: Incorporating 3d Laser Scanning Into Bimmentioning
confidence: 99%
“…It is indicated that the proposed method could generate as-is BIMs with more accuracy in terms of geometric and semantic information. Aricò and Brutto [46] applied the Scan-to-BIM method to the survey and spatial modelling of a historical building, the Arab-Norman church in Palermo, to be exact. The 3D laser scanning and Photogrammetry techniques were employed to collect the data from the asset.…”
Section: Incorporating 3d Laser Scanning Into Bimmentioning
confidence: 99%
“…An essential task related to the management of historic objects including monitoring their state of preservation or planning activities for their conservation and ongoing maintenance, is the development of a reliable 3D model (Aricò and Brutto. 2022;Rocha et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…These methods allow the creation of parametric models in a BIM (Building Informaton Modeling) environment, which are able to improve the geometric model under development. It should be noted that BIM technology also enables the integration of different types of data (Aricò and Brutto. 2022;Rocha et al, 2020).…”
Section: Introductionmentioning
confidence: 99%